Deteksi Awal Aktivitas Antibakteri dari bakteri air tambak terhadap bakteri patogen akuakultur - Stella Magdalena; Sindy Sindy; Yogiara Yogiara (Biota, 2020)
Aquaculture is currently experiencing massive loss due to the outbreak of pathogenic bacteria. One of the outbreak causes is the development of pathogenic bacterial resistance to the antibacterial. The problem can be solved using microorganisms that can produce new antibacterial compounds. The purpose of this research was to obtain bacteria from fishpond water that could produce antibacterial compounds. About two out of 81 isolates could produce antibacterial compounds. Those two isolates were obtained from saltwater fishponds in North Jakarta (TS2) and Harapan Island (PHY). All fishpond water was grown in marine broth or Luria broth. Extraction of antibacterial compounds was performed using four types of solvents: chloroform, dichloromethane, ethyl acetate, and methanol. Each of the solvents showed a different result. The extraction can only be successfully performed using chloroform and dichloromethane. Extraction using dichloromethane showed a larger inhibitory clear zone than chloroform. Based on 16S rRNA gene sequencing, PHY isolate was identified as Bacillus sp. and TS2 as Acinetobacter sp. In conclusion, isolate TS2 and PHY, which produced antibacterial compounds, showed potential use as aquaculture probiotics.